2015
DOI: 10.1097/01.dss.0000452650.06765.51
|View full text |Cite
|
Sign up to set email alerts
|

Light-Emitting Diode–Generated Red Light Inhibits Keloid Fibroblast Proliferation

Abstract: Light-emitting diode-generated red light can inhibit keloid fibroblast proliferation in a dose-dependent manner without altering viability. Light-emitting diode-generated red light has the potential to contribute to the treatment of keloids and other fibrotic skin diseases and is worthy of further translational and clinical investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Following irradiation, experimental and matched control dishes were returned to the incubator and then harvested for relevant assays at the appropriate time‐course. Doses for irradiation were selected based upon our pilot irradiation studies and prior studies .…”
Section: Methodsmentioning
confidence: 91%
“…Following irradiation, experimental and matched control dishes were returned to the incubator and then harvested for relevant assays at the appropriate time‐course. Doses for irradiation were selected based upon our pilot irradiation studies and prior studies .…”
Section: Methodsmentioning
confidence: 91%
“…LED-RL fluences were selected based upon previously published studies that demonstrated LED photoinhibition of skin fibroblast proliferation. [ 7 , 9 , 10 ]…”
Section: Methodsmentioning
confidence: 99%
“…Light-emitting diode (LED) is a PBM feature when the light emission is non-coherent and non-collimated. The biostimulatory effects of LEDs exert an anti-inflammatory as well as anti-fibrotic effects resulting in the release of inflammatory mediators [114][115][116] and fibroblast proliferation inhibition [117].…”
Section: Light Emitted Diodes (Leds)mentioning
confidence: 99%